Teleseismic body wave inversion - Moshou, A.; Papadimitriou, P.; Makropoulos, K. (Bulletin of the Geological Society of Greece, 2007)
Body wave inversion methodology is developed to determine the earthquake source parameters in teleseismic distances. The generalized inversion technique, based on the singular value decomposition method, is applied to determine the deviatone moment tensor which is decomposed in two parts. The first one is related to the pure Double Couple (DC) and the second one to the compensated linear vector dipoles (CLVD). The best solution of the overdetermined problem is obtained by minimizing the misfit between observed and synthetic seismograms. The proposed methodology is applied for the four strongest earthquakes that occurred recently in Greece (2001-2006)